2020
DOI: 10.3389/fmicb.2020.01384
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Polycistronic Expression in the Model Microorganism Ustilago maydis

Abstract: Eukaryotic microorganisms use monocistronic mRNAs to encode proteins. For synthetic biological approaches like metabolic engineering, precise co-expression of several proteins in space and time is advantageous. A straightforward approach is the application of viral 2A peptides to design synthetic polycistronic mRNAs in eukaryotes. During translation of these peptides the ribosome stalls, the peptide chain is released and the ribosome resumes translation. Thus, two independent polypeptide chains can be encoded … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
(100 reference statements)
0
22
0
1
Order By: Relevance
“…Photinus pyralis luciferase FLuc was recently established for intracellular use in U. maydis ( Müntjes et al, 2020 ). Bioluminescence would be a straight-forward alternative read-out for unconventional secretion because the signal can be detected directly from the culture broth while the established reporters Gus and β-galactosidase (LacZ) require more elaborate biochemical assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photinus pyralis luciferase FLuc was recently established for intracellular use in U. maydis ( Müntjes et al, 2020 ). Bioluminescence would be a straight-forward alternative read-out for unconventional secretion because the signal can be detected directly from the culture broth while the established reporters Gus and β-galactosidase (LacZ) require more elaborate biochemical assays.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a FLuc-Jps1 expressing strain was generated (AB33P8∆/FLuc-Jps1) to evaluate the effect of the alternative carrier ( Figure 3B ). AB33 producing intracellular luciferase (FLuc Cyt ) was used as a positive control in all assays ( Müntjes et al, 2020 ). Monitoring of proliferation revealed that growth speed was slightly reduced in AB33P8∆/FLuc-Jps1 with a doubling time of 3.5 h, compared to the progenitor strain AB33P8Δ and AB33P8∆/FLuc-Cts1 showing doubling times of 3 h in the exponential growth phase ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…4B, top; Brachmann et al ., 2001). To investigate dynamic endosomal transport, we used strains expressing functional C-terminal fusion Upa1-Gfp and Rrm4-Kat (fusion with enhanced version of the green fluorescent protein, Clontech, and monomeric version of red fluorescent protein mKate2, respectively; Müntjes et al ., 2020; Pohlmann et al ., 2015; see Materials and methods).…”
Section: Resultsmentioning
confidence: 99%
“…To validate qualitatively whether these results also hold true for full-length proteins, we performed yeast two-hybrid experiments comparable to previous studies (Pohlmann et al ., 2015). To this end, Upa1 or Rrm4 versions were fused at the N-terminus with the DNA-binding domain (BD) and activation domain (AD) of Gal4p, respectively (see Materials and methods; the C-termini were fused with the enhanced version of the green fluorescent protein [Gfp], Clontech; or the monomeric version of red fluorescent protein mKate2 [Kat], respectively; Müntjes et al ., 2020; Pohlmann et al ., 2015). Rrm4-Kat interacts with full-length Upa1-Gfp (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation